Portable personal conditioning systems: Transient modeling and system analysis. (15th December 2017) - Dhumane, Rohit; Ling, Jiazhen; Aute, Vikrant; Radermacher, Reinhard
Highlights: A new concept of portable personal conditioning system introduced. Expected building energy savings in the range 10–30% with improved thermal comfort. Equations for multi-domain dynamic modeling of four such systems discussed. Weight, battery performance, cost comparison calculated for each system. Payback period and economic considerations of the technology discussed. Abstract: The existing Personal Conditioning Systems (PCS) have a limited market potential in spite of their energy savings potential and improved thermal comfort due to a combination of factors like retrofit costs, cooling limited to regions near installation and addition to building heat loads. We propose a novel concept of Portable Personal Conditioning System (PPCS) to address these challenges. PPCS includes a cooling system on an automated platform, which follows occupants to keep them comfortable. Four such cooling systems are presented: a vapor compression system (VCS), a chilled water based system, an ice storage based system and a phase change material storage based system. First-principles-based, transient multi-physics models were constructed for each system using Modelica to gain a more complete understanding of system performance and to quantify performance criteria such as minimum system weight and battery life. The article quantifies the trade-offs from the use of each system and is expected to motivate the development of portable personal cooling devices. System weights range from 19 to 31 kg with the chilled water system being the heaviest. The VCS consumes 40% more battery while delivering 170 W cooling at roughly twice the price of the chilled water system. The ice and phase change material based systems have weights comparable to the VCS and power consumption comparable to that of the chilled water based system.